2020
DOI: 10.1029/2019jc015226
|View full text |Cite
|
Sign up to set email alerts
|

Tide‐Induced Periodic Sea Surface Temperature Drops in the Coral Reef Area of Nanwan Bay, Southern Taiwan

Abstract: Tidal current-induced cyclonic eddies cause cold-water upwelling and periodic sea surface temperature (SST) drops around the coral reef area in Nanwan Bay, which is located at the southern tip of Taiwan. This study used Himawari-8 satellite data and tide gauge and coastal ocean dynamics application radar (CODAR) data to analyze the characteristics of the SST drops and cyclonic eddy propagation and used an oceanic general circulation model (OGCM) to simulate the tidal current flowing process. According to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…Fox et al 51 demonstrated that in regions with relatively high primary production (as gauged by chlorophyll-a levels), corals are consistently more heterotrophic. The highest chlorophyll-a values reach 0.8 mg m −3 , with the monthly average between 0.17 and 0.37 mg m −3 (annual mean = 0.25 mg m −3 ) in Nanwan Bay 52 . Such high variation is due to upwelling of cold seawater and nutrients, the latter of which stimulate phytoplankton growth and thereby leads to increased chlorophyll-a concentrations at our study site 53 .…”
Section: Discussionmentioning
confidence: 96%
“…Fox et al 51 demonstrated that in regions with relatively high primary production (as gauged by chlorophyll-a levels), corals are consistently more heterotrophic. The highest chlorophyll-a values reach 0.8 mg m −3 , with the monthly average between 0.17 and 0.37 mg m −3 (annual mean = 0.25 mg m −3 ) in Nanwan Bay 52 . Such high variation is due to upwelling of cold seawater and nutrients, the latter of which stimulate phytoplankton growth and thereby leads to increased chlorophyll-a concentrations at our study site 53 .…”
Section: Discussionmentioning
confidence: 96%
“…This includes periodic variations in ocean currents registered by moored instruments or acoustic tomography (Dushaw et al., 1997; Luyten & Stommel, 1991; Ray, 2001) as well as by induced secondary magnetic fields (Maus & Kuvshinov, 2004; Saynisch et al., 2018), sea surface height changes measured from tide gauges and satellite altimetry (Doodson, 1928; Schrama & Ray, 1994), and global bottom pressure variations from pelagic pressure recorders and gravimetric satellite missions (Wiese et al., 2016). More recently, even tiny variations in sea surface temperature (Hsu et al., 2020) and tropical precipitation observations (Kohyama & Wallace, 2016) were related to ocean tidal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-based Sea Surface Temperature (SSTs) estimations can be crucial for large-scale studies or locations that are difficult to access ( Van Hooidonk & Huber, 2009a ; Van Hooidonk & Huber, 2009b ; Burt et al, 2019 ). However, the specific environmental context of certain areas—such as KNP, where tide-associated upwelling and recurrent typhoons induced important smaller scale seawater temperature variations ( Keshavmurthy et al, 2019 ; Hsu et al, 2020 ; Lee et al, 2020 )—are not likely to be identified by satellite data; this may have misguided estimates of the capacity of reefs to resist large-scale heat-stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In the bay of Nanwan, a tidal upwelling can cause further sudden temperature drops as the topography of the bay induces the formation of cyclonic eddies. These eddies move from west to east throughout the bay, during the ebb tidal current, mixing the cooler deeper seawater layers with the warmer shallow ones ( Lee et al, 1997 ; Lee et al, 1999 ; Hsu et al, 2020 ). The upwelling within Nanwan has been shown to play an important role in the physiology of marine organisms in the area ( Chen et al, 2005 ; Keshavmurthy et al, 2019 ), especially during summer periods, when the upwelling can cause daily variations in seawater temperatures to increase by up to 2.5 °C ( Hsu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation